Transmedia sports: the game Cartola and new ways of cheering in the Brazilian Soccer Championship (Intercom - Brazilian Journal of Communication Sciences, 2022)
This article aims to study how transmedia storytelling reflects how Brazilian supporters engage with Brazilian Soccer League – Brasileirão – through the game Cartola. This game consists of a fictitious competition in which users must create and line up teams based on real soccer players to challenge other users. For this reason, the concept of transmedia storytelling is a key base in this work. Transmedia represents a process in which content elements get spread across multiple platforms in a coordinated manner. As a corpus of analysis, we collected content broadcasted on TV during the rounds of October 2019, in addition to social networks, specifically Twitter, Cartola’s official website and app. We noticed that the game contributes to increasing the fans’ engagement with the national championship and changes the current logic in the ways of supporting and in the communicational and social interactions related to football.
Keywords: Cartola; Gamification; Transmedia storytelling; Soccer; Interaction